2020
DOI: 10.9734/arrb/2020/v35i230187
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mutagenic Action of Ruta chalepensis against Rat Sperm Cell Abnormalities-induced by Potassium Bromate

Abstract: Aims:The aim of current study was to investigate the genotoxic damage of potassium bromate on sperm cell morphology and the potential defense role of Ruta chalepensis (Rue) against the potassium bromate effects. Study Design: Fifty rats (Strain: Rattus norvegicus) were randomly divided into five groups (10 rats/group) as follows: (Control group) received distilled water daily for 4 weeks, (KBrO 3 group) treated with KBrO 3 (100 mg/kg/b.w) for 4 weeks, (Rue group) received Rue orally in a daily dose (0.5 g/anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…According to the data in table 1 and 2, the results were similar to [16] who reported that potassium bromate induced sperm cells abnormalities of treated animals. In addition, these results were similar to [17] who reported that potassium bromate clearly had mutagenic effects and caused several types of abnormalities in sperm cells. Furthermore, these results supported by [18] They discovered that potassium bromate hampered male reproductive processes and caused infertility in male Wistar rats by increasing abnormalities in sperm and decreasing sperm quality, as well as by altering sperm morphology, motility, and viability.…”
Section: Discussionsupporting
confidence: 90%
“…According to the data in table 1 and 2, the results were similar to [16] who reported that potassium bromate induced sperm cells abnormalities of treated animals. In addition, these results were similar to [17] who reported that potassium bromate clearly had mutagenic effects and caused several types of abnormalities in sperm cells. Furthermore, these results supported by [18] They discovered that potassium bromate hampered male reproductive processes and caused infertility in male Wistar rats by increasing abnormalities in sperm and decreasing sperm quality, as well as by altering sperm morphology, motility, and viability.…”
Section: Discussionsupporting
confidence: 90%